دور البحث والتطوير في رفع تنافسية المؤسسات الاقتصادية في سورية (Latakia University Journal - Economic and Legal Sciences Series, 2013)
يمر العالم اليوم بموجة من التغييرات والتطورات المتسارعة في شتى مجالات الحياة  السياسية والاقتصادية والاجتماعية والثقافية , ويعود ذلك على التقدم الهائل في تكنولوجيا  المعلومات والاتصالات التي جعلت من العالم قرية واحدة الأمر الذي يؤدي إلى تغييرقواعد التنافسية الدولية . وسورية التي تعتبر جزء هاماً من هذا العالم بحكم موقعها الجيو استراتيجي , تؤثر وتتاثر بما يحدث في هذا العالم ,وبالتالي يحتم عليها زيادة قدراتها التنافسية. ويشكل البحث العلمي  والتطوير مرتكزاً أساسياً للتنافسية و مطلباً هاماً للتنمية لأنه يعمل على تغيير ملامح المؤسسات الإنتاجية السورية ويساعدها على الارتقاء إلى المستوى المرموق . فالاستثمار في البحث والتطوير سيؤدي عموماً إلى تحسين الناتج المحلي الإجمالي. وتتأتي ضرورة الاستثمار في البحث والتطوير من واقع أن أي اقتصاد مستدام هو اقتصاد مبني على المعرفة وذلك في كل القطاعات. ويتطلب هذا الأمر تعبئة جميع الفاعلين المعنيين، بدءاً من الحكومة ومروراً بالمنظمات غير الحكومية والقطاع الخاص والمنظمات الدولية والإقليمية ومجتمع العلوم والتقانة وانتهاءاَ بوسائل الإعلام.The world is undergoing today a wave of changes and rapid developments in various areas: political, economic, social and cultural. This is due to the tremendous progress in information and communication technology that turned the world into one village. This, in turn, leads to a transformation in international competitiveness rules. Syria, which is an important part of this world by virtue of its geo-strategic location, affects and is affected by what happens in this world. Thus, it is necessary for this country to increase its capabilities of competitiveness. Research and development are a major anchor of competitiveness and an important requirement for growth because they work to change the features of Syrian productive enterprises and help them to upgrade to a prestigious level. Investing in research and development will generally improve the GDP. The need to invest in research and development is derived from the fact that a sustainable economy is an economy based on knowledge, in all sectors. This requires the mobilization of all active entities concerned, including the government, NGOs, the private sector, international and regional organizations, the of science and technology community and the media.